2015
DOI: 10.1016/j.compedu.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The wear out effect of a game-based student response system

Abstract: The Bring Your Own Device (BYOD) wave and advancement in technical infrastructures and in learning technology opens for new ways of teaching in the classroom. The teachers' laptops connected to a video projector, access to wireless network and the students smartphones, tablets or laptops can be utilized to enhance the interaction between the teacher and students, as well as boost the students motivation, engagement and learning. The introduction of new learning technology in the classroom normally results in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
325
2
84

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(434 citation statements)
references
References 28 publications
23
325
2
84
Order By: Relevance
“…Alanyazında, Kahoot'un oluşturduğu yarışmacı, bağlayıcı, eğlenceli ortamın öğrenmeye teşvik eden eğlenceli ve yarışmacı bir ortam sunarak öğrencilerin heyecanla sınıfa gelmelerini sağladığı (Dellos, 2015), sınıf içinde oyun ve eğlence unsurlarına vurgu yaparak öğrencilerin interaktif şekilde derse katılımını sağladığı (Underdal ve Sunde, 2014) ve tekrar tekrar kullanılmasına rağmen öğrencilerin derse bağımlılığını yüksek düzeyde tuttuğu (Wang, 2015), odaklanma, bağlanma, eğlenme, motivasyon ve memnuniyet üzerinde Kahoot'un olumlu etkileri olduğu (Chaiyo ve Nokham, 2017), görülmüştür. Yapılan çalışmada elde edilen sonuçlara göre Kahoot ile desteklenen öğrenme ortamı; rekabetçi, eğlenceli ve güdüleyici olması yönüyle alanyazındaki sonuçlarla benzerlik göstermektedir.…”
Section: Tartişma Ve Sonuçunclassified
See 1 more Smart Citation
“…Alanyazında, Kahoot'un oluşturduğu yarışmacı, bağlayıcı, eğlenceli ortamın öğrenmeye teşvik eden eğlenceli ve yarışmacı bir ortam sunarak öğrencilerin heyecanla sınıfa gelmelerini sağladığı (Dellos, 2015), sınıf içinde oyun ve eğlence unsurlarına vurgu yaparak öğrencilerin interaktif şekilde derse katılımını sağladığı (Underdal ve Sunde, 2014) ve tekrar tekrar kullanılmasına rağmen öğrencilerin derse bağımlılığını yüksek düzeyde tuttuğu (Wang, 2015), odaklanma, bağlanma, eğlenme, motivasyon ve memnuniyet üzerinde Kahoot'un olumlu etkileri olduğu (Chaiyo ve Nokham, 2017), görülmüştür. Yapılan çalışmada elde edilen sonuçlara göre Kahoot ile desteklenen öğrenme ortamı; rekabetçi, eğlenceli ve güdüleyici olması yönüyle alanyazındaki sonuçlarla benzerlik göstermektedir.…”
Section: Tartişma Ve Sonuçunclassified
“…Kahoot is an online application that plays an important role in the gamified assessment programs and can contribute to the success of the students at different learning levels (Underdal and Sunde, 2014). Wang (2015) found that students quizzed with Kahoot learned 22% more and motivated 25% more than those who quizzed on paper. Iwamoto, Hargis, Taitano, Vuong (2017) indicated that in examinations involving the future of students, pedagogical tools such as the Kahoot could be used at college and university level to improve the test results.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Huotari e Hamari (2012), gamificação também pode ser definida como o melhoramento de tarefas para que as mesmas se tornem mais motivadoras, por meio do uso de elementos de design de jogos. Com base nesta ideia, Wang (2015) desenvolveu o conceito de GSRS (Game-Based Student Response Systems), que se trata de um tipo de SRS baseado em gamificação (gamificado). A partir do conceito de GSRS, Wang (2015) criou o Kahoot!…”
Section: Introductionunclassified
“…Players´ attention in game-based learning has been found to be correlated to learning effects [43]. In a study conducted by Wang [44] using Kahoot! students reported that they got more engaged in the lecture "when it was spiced up with something fun and exciting that made it possible to keep or re-establish the attention" [44, p. 224].…”
Section: Attention and Attitudementioning
confidence: 99%